2010
DOI: 10.1210/me.2010-0005
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of the Mineralocorticoid Receptor N-terminal Domain: Evidence for Induced and Stable Structure

Abstract: The mineralocorticoid receptor (MR) binds the steroid hormones aldosterone and cortisol and has an important physiological role in the control of salt homeostasis. Regions of the protein important for gene regulation have been mapped to the amino-terminal domain (NTD) and termed activation function (AF)1a, AF1b, and middle domain (MD). In the present study, we used a combination of biophysical and biochemical techniques to investigate the folding and function of the MR-NTD transactivation functions. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 54 publications
(14 reference statements)
6
43
0
Order By: Relevance
“…4). The affinity and kinetics are similar to that reported for TBP C binding with NTDs of GR, MR, and ER␣ (31,33,36). The onand off-rates are consistent with a two-step model that involves a fast initial binding event and a slower dissociation once the complex is formed due to structural rearrangements that form a more stable conformation (31,33).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…4). The affinity and kinetics are similar to that reported for TBP C binding with NTDs of GR, MR, and ER␣ (31,33,36). The onand off-rates are consistent with a two-step model that involves a fast initial binding event and a slower dissociation once the complex is formed due to structural rearrangements that form a more stable conformation (31,33).…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies, conditional folding of the NTD of GR and MR induced by osmolytes or TBP was shown to facilitate binding of co-activators such as SRC-1, -2, and -3, CBP and co-repressors SMRT and RIP140 (31,33). Conditional folding by TBP also enhanced the ability of SRC-1 to stimulate GR or MR NTD-dependent transcriptional activity.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Consistent with the properties of IDPs, AR interacts with more than 160 proteins (22), and proteinprotein interactions with the activation function-1 (AF1) region in the NTD are essential for AR transcriptional activity (23)(24)(25)(26). AR NTD has less than 15% homology with other steroid receptors that also have predominantly intrinsically disordered NTDs (27)(28)(29)(30)(31). Malleability of intrinsically disordered NTDs of these transcription factors is crucial for their function that requires interactions with many binding partners.…”
Section: Introductionmentioning
confidence: 92%